Pertinent ills concomitant with matrifocality in Zimbabwe : implications for development - Mafa, Itai (Innovare Academic Sciences, 2021)
Objective: The paper explored the challenges underpinning matrifocality in Zimbabwe, what is normally termed single motherhood. With the marital institution losing eminence in Africa due to a myriad of factors such as globalization, industrialization, and eurocentrism; this has greatly altered today’s family structure. The study was anchored on the realization that the traditional composition of an African family which recognized extended families has now been overshadowed by the surfacing of nuclear families as well as an increase in matrifocal families.